Grain quality of spring wheat varieties (Mongolian Journal of Agricultural Sciences, 2017)
Spring wheat is main crop of Mongolia and sown more 90% of agricultural planting area. Total wheat production of Mongolia are increasing gradually, but out of strong and valuable wheat for bread and flour production. Main case of providing sustainable wheat production are develop and widely cultivate strong and valuable wheat varieties resistant to abiotic stresses, with high yield and good quality. Spring wheat varieties by HMW-GS loci were similar, but variety Darkhan-166 /Arvin/ was more than others varieties. Wheat varieties Darkhan-144, KP-547-12, Darkhan-131, Darkhan-144 and KP-561-12 have a high 1000 grain weight (41.5-44.8 g). Spring wheat varieties KP-547-12, Darkhan-131 and KP-561-12 have a high dry gluten content (13.1-14.2%). Water absorption of spring wheat varieties were 61-62% and by this parameters Darkhan-131, Darkhan-166 and KP-547-12 varieties were a high. Dough development time of wheat varieties were 8-13 мин and Darkhan-131, Darkhan-166, Darkhan-172 and KP-547-12 varieties have a high flour power. Wheat varieties Darkhan-131 and KP-547-12 have a high dough energy (828.8-857.2 g.mm).